SOSIALISASI PENGURANGAN PENYEBARAN COVID-19 MELALUI BANNER DI KELURAHAN WONOREJO KECAMATAN TEGALSARI KOTA SURABAYA - Esti Puji Rahayu; Syifa Syarifah Alamiyah; Velia Audi Hervitya; Lidya Britania Putong; Agil Satriyo Adji (Jurnal Pengabdian NUSANTARA, 2021)
Indonesia is experiencing a significant increase in the spread of Covid-19 cases, especially in the middle of 2021. Efforts made by the government to reduce the spread of Covid-19 include instructions for implementing the 5M health protocol (Wearing masks, Washing hands, Keeping distance, Staying away from crowds, Reducing mobility). ) and Vaccination. The purpose of this community service activity is to educate the community, especially the community around Wonorejo Village, Tegalsari District, Surabaya City to increasingly implement and comply with the 5M health protocol and support the government's vaccination program so that the spread of Covid-19 can be reduced. The method applied in community service activities by this group of 10 Thematic National Defense Community Service Programs is by conducting education using a media banner about Steps to restore the situation in Indonesia through the government's vaccination program, as well as complying with the 5M health protocol and vaccination based on the Covid-19 prevention protocol of the Ministry of Health. Republic of Indonesia. The results of community service carried out by a group of 10 Thematic National Defense Community Service Programs in 2021, making and installing 5M banners and vaccinations in the Wonorejo Village, Tegalsari District, Surabaya City can run well